Evaluation of IPM modules against major sucking insect pests of groundnut (Arachis hypogaea) - PRIYANKA,; KHINCHI, S K; HUSSAIN, AKHTER; SHARMA, S L; CHOUDHARY, SUMAN; PIPLODA, SANJU (The Indian Journal of Agricultural Sciences, 2023)
Groundnut (Arachis hypogaea L.) is one of the major oilseed crops, contributing 45% of oilseed production in India. Being a cash crop, groundnut helps farmers to support themselves and their families. Additionally, it gives farm families access to nutrient-dense groundnut kernels, which are high in protein and energy and it also provides nutritious fodder (haulms) to livestock. Insect pest menace is one of the few essential biotic stresses contributing towards lower yield. The sucking pests like aphids, leafhoppers and thrips are the major biotic constraints for a crop like groundnut. Currently, farmers are accustomed to using synthetic insecticides to control their infestation. Unregulated insecticide use may also endanger farm-friendly insects. This practice must be replaced with some other methodologies such as integrated pest management modules. Therefore, present study was carried out to evaluate 11 different IPM modules including untreated (control) against sucking insect pests of groundnut during rainy (kharif) season of 2020 and 2021 at Sri Karan Narendra Agriculture University, Jobner, Rajasthan. The maximum per cent reduction in sucking insect pests populations was observed in module M10 (farmer practices-imidacloprid) and mentioned as effective IPM module. The maximum pod yield of 27.08 q/ha was also obtained in the module M10. On the basis of cost benefit (B:C) ratio the module M10 gave the highest ratio (25.62) followed by M7 (12.35) and M1 (12.15).